The World House Remodeled: Toward Beloved Community Through Housing Justice - Montague, Terri Y. (Journal of law and religion, 2024)
In Where Do We Go from Here: Chaos or Community? the Reverend Dr. Martin Luther King, Jr. speaks with conviction on the need for and importance of community. King depicts American society and modern civilization as a great "world house" that is inhabited, inherited - and imperiled. Behind the metaphor of the world house is a prophetic vision and dream - the realization of what he called the "beloved community." In this article, the author considers King’s beloved community ideal through a housing lens. Engaging with King's metaphor, the author frames the beloved community as an apologetic for integrated community. The author views the metaphor of the world house as a significant means to expand understanding of beloved community, elevate housing as a moral-ethical concern, and engender radical structural solutions that can be realized through racial justice in the housing sector.